ASSESSMENT OF THE SEVERITY OF BURN INJURY CONSIDERING BIOCHEMICAL AND IMMUNOLOGICAL FEATURES - Hamdullayeva N.,; Kudratova Z.E., (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
The development of new methods and research programs, both for cellular and molecular composition of human biological fluids and their integration into clinical laboratory diagnostics, contributes to enhancing the effectiveness of disease treatment and reducing the duration of temporary incapacity for the affected individuals. In this regard, identifying new approaches for clinical laboratory diagnostics in burn medicine remains relevant [1,2].